Asset pricing with nonlinear consumption services - Morais, Bruno Ferreira de (2023)
When the service flow from durable goods is taken to be linear on the stock of durables, the dynamics of of the latter are heavily dependent on the former. This allows the CCAPM to attain greater levels of consumption risk, helping to solve some of the many financial puzzles that surround the model. However, we argue that this implementation should not be taken for granted. We investigate an alternative approach to quantify the flow of services from durable goods. Our findings indicate that durables consumption has the potential to decrease, rather than increase, the consumption risk that households encounter.